Strategic Management In Enhancing The Competitiveness Of Msmes In Jayawijaya Regency, Wamena - Mikaus Gombo; Ahmad Walela; Lazarus Suyatno Vianney (Eduvest - Journal of Universal Studies, 2025)
This study aims to describe the implementation of strategic management by Micro, Small, and Medium Enterprises (MSMEs) in Jayawijaya Regency and to analyze the internal and external factors affecting their competitiveness. A descriptive qualitative approach was used, with data collected through in-depth interviews, direct observation, and documentation. The findings reveal that most MSME actors do not formally apply strategic management but tend to adopt informal strategies based on experience and intuition. Internal factors affecting competitiveness include low managerial capacity, limited capital, and lack of innovation. External factors include inadequate infrastructure, restricted access to digital markets, and insufficient business mentoring. Strategies to improve competitiveness involve entrepreneurship training, utilizing local potential, multi-stakeholder collaboration, and applying simple technologies. This study provides recommendations for local governments, business actors, and supporting institutions to design contextual and sustainable MSME development strategies in frontier, outermost, and underdeveloped (3T) regions such as Jayawijaya.